Integrating quantum materials into superconducting qubits - Kuei-Lin Chiu; Avishma J Lasrado; Cheng-Han Lo; Chung-Ting Ke; Vahid Mosallanejad; Yen-Hsiang Lin (Materials for Quantum Technology)
In this perspective article, we review the current state of research on integrating quantum materials (QMs) into superconducting quantum devices. We begin with the role of QMs as weak links in Josephson junctions, enabling gate- and flux-tunable transmons. We then explore their application in more complex superconducting circuits, such as gate-tunable fluxonium qubits, or gatemonium, which provide additional control over qubit parameters. We also discuss QM-based vertical junctions and their potential for creating merged-element transmons. Further, we highlight QMs’ role in topological superconducting circuits, where they facilitate the study of Majorana zero modes through signatures such as 4 π -periodic supercurrents. Additionally, we review the integration of QMs into 3D cavity architectures and discuss how they differ from their 2D counterparts. Beyond weak links, we examine the use of 2D superconducting and insulating materials, such as NbSe _2 and hBN, in parallel-plate capacitors, offering a compact alternative to conventional large-footprint transmon capacitors. Finally, we outline the current challenges and future directions for exploration.